2018
DOI: 10.5198/jtlu.2018.1054
|View full text |Cite
|
Sign up to set email alerts
|

Mobility tools and use: Accessibility’s role in Switzerland

Abstract: In much of Switzerland, public transport offers high levels of accessibility to workplaces and other places that make season tickets legitimate substitutes for a car. These similar patterns of accessibility provided by both modes result in high levels of correlation between the accessibility measures of both modes. This correlation almost always precludes a travel behavior analysis with several accessibility measures and cannot provide any insights into the effects of the differences in accessibility levels by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…For mobility scholars, having access to the city and its resources is inescapably tied to a getting to component that is only possible through the fulfilment of the right to mobility across urban space (Verlinghieri and Venturini, 2018). Nevertheless, scholarly approaches to mobility still rely a great deal on the movement of bodies across urban space through an array of private and public mobility resources (Kowald et al, 2017; Le Vine et al, 2013; Loder and Axhausen, 2018). I contend that the literature on mobility still lacks the analytical tools to fully grasp the land-use and socio-economic dimensions of accessibility to jobs.…”
Section: Discussionmentioning
confidence: 99%
“…For mobility scholars, having access to the city and its resources is inescapably tied to a getting to component that is only possible through the fulfilment of the right to mobility across urban space (Verlinghieri and Venturini, 2018). Nevertheless, scholarly approaches to mobility still rely a great deal on the movement of bodies across urban space through an array of private and public mobility resources (Kowald et al, 2017; Le Vine et al, 2013; Loder and Axhausen, 2018). I contend that the literature on mobility still lacks the analytical tools to fully grasp the land-use and socio-economic dimensions of accessibility to jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few authors (4,5,43) have discussed commitment devices within transport choices. Simma and Axhausen (4, 5) look into the difference in car and public transport use between those who own a car or a transport pass.…”
Section: Introductionmentioning
confidence: 99%
“…Simma and Axhausen (4, 5) look into the difference in car and public transport use between those who own a car or a transport pass. Loder and Axhausen (43) additionally include data on trips made by soft transport (cycling or walking). The authors concluded that they found evidence of commitments to transport modes, as the consumers who own or have access to a particular mobility device (i.e., a car or public transport using a discount pass), use that mode relatively more.…”
Section: Introductionmentioning
confidence: 99%
“…Only few authors Axhausen, 2001, 2003;Loder and Axhausen, 2018) have discussed commitment devices within transport choices. Axhausen (2001, 2003) look into the difference in car and public transport use between those who own a car or a transport pass.…”
Section: Introductionmentioning
confidence: 99%
“…Axhausen (2001, 2003) look into the difference in car and public transport use between those who own a car or a transport pass. Loder and Axhausen (2018) additionally include data on trips made by soft transport (cycling or walking). The authors conclude that they find evidence of commitments to transport modes as the consumers who own or have access to a particular mobility device (i.e.…”
Section: Introductionmentioning
confidence: 99%